A novel scoring system to predict the residual back pain after percutaneous kyphoplasty for osteoporotic vertebral compression fracture - Yang, Dongjun; Liu, Xin; Zhou, Yang; Xu, Yong; Huang, Qiangkai (Frontiers in Surgery, 2022)
Objective To establish a scoring system to predict the residual back pain after percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fracture (OVCF). Materials and methods We retrospectively reviewed the clinical records of 98 patients who were diagnosed of single-vertebral OVCF and underwent PKP surgery in our department from January 2015 to December 2017. The following clinical characteristics including age, gender, disease course, fracture location, fracture type, segmental kyphosis, and bone cement volume were all recorded, and the effects of these factors on postoperative pain (at 1-month and 6-month postoperative) were also analyzed respectively. Based on 6-month postoperative VAS score, the included patients were divided into two groups, namely the residual back pain group (19 patients) and the non-residual back pain group (79 patients). The independent risk factors of residual back pain after PKP were screened and the scoring system was established by the multivariate logistic regression analysis. The performance of this scoring system was also prospectively validated using the clinical data of 45 patients with single-vertebral OVCF from January 2018 to December 2019. Results The scoring system was consist of five clinical characteristics which were confirmed as significant predictors of residual back pain after PKP, namely, age ≥ 60 years (P=0.021), fracture location = thoracic or lumbar (P=0.002), fracture type = OF4 type (P=0.018), segmental kyphosis ≥ 20° (P=0.014), and bone cement volume < 5 ml (P=0.001). Patients in the residual back pain group showed a significant higher score than the non-residual back pain group (6.84±1.71 vs. 2.66±1.97, t=8.499, P<0.001), and the optimal cut-off value for the scoring system was 5 points. The sensitivity and specificity of the scoring system for predicting residual back pain after PKP were 84.21% and 87.34%, respectively, in derivation set and 78.57% and 83.87% in validation set. Conclusion This novel scoring system showed satisfactory diagnostic efficacy in predicting residual back pain after PKP for single-vertebral OVCF. Patients with the score of 5 to 9 had a high risk of postoperative residual back pain, while the patients with score of 0 to 4 was low.